2018
DOI: 10.3389/fevo.2018.00154
|View full text |Cite
|
Sign up to set email alerts
|

Common Practice Solvent Extraction Does not Reflect Actual Emission of a Sex Pheromone During Butterfly Courtship

Abstract: Olfactory communication can be of critical importance for mate choice decisions. Lepidoptera are key model systems for understanding olfactory communication, particularly considering sex pheromone signaling in the context of sexual selection. Solvent extraction or rinsing of pheromone-producing structures is a widespread method for quantifying sex pheromones, but such measures reflect what is stored and may not represent what is actually emitted by an individual during courtship. Here, we address this point fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…132 Headspace analyses showed that males can actively control MSP emission and adjust to an increased male–male competition. 137 Other effects such as phenotypic plasticity in MSP production, 124 geographical variation, likely driving reproductive isolation and speciation, 138 reproductive character displacement MSP composition of different Bicyclus species, 123 learning of visual signals in mate choice, 139 and plastic female preferences for a male pheromone odour blend influenced by early pheromone odour experiences 140 have been studied.…”
Section: Satyrinaementioning
confidence: 99%
See 3 more Smart Citations
“…132 Headspace analyses showed that males can actively control MSP emission and adjust to an increased male–male competition. 137 Other effects such as phenotypic plasticity in MSP production, 124 geographical variation, likely driving reproductive isolation and speciation, 138 reproductive character displacement MSP composition of different Bicyclus species, 123 learning of visual signals in mate choice, 139 and plastic female preferences for a male pheromone odour blend influenced by early pheromone odour experiences 140 have been studied.…”
Section: Satyrinaementioning
confidence: 99%
“…141 A comparison of wing extraction and headspace sampling methods underlined the importance and differences of sampling methods. 137 While wing extracts only reflect stored compounds, it does not necessarily represent the compounds actually emitted during courtship. Whereas headspace analysis maybe better at representing the released scent, although valid for a confined space, it is not known if it is comparable to what a female receives.…”
Section: Satyrinaementioning
confidence: 99%
See 2 more Smart Citations